Analysis of Marketing Strategies in Increasing Patient Satisfaction Using SWOT Analysis at Voluntary Healthy Clinic in Pondok Aren, South Tangerang - Fauziah Septiani (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to find out what kind of marketing strategy should be used to increase patient satisfaction and also to identify the strengths, weaknesses, opportunities and threats that exist at the Voluntary Healthy Clinic. This research uses qualitative research with a case study approach. Primary data was collected through interviews with several clinic stakeholders. Apart from using the interview method, the author also uses observation and documentation methods to deepen the data obtained. The data that has been collected is then analyzed using the SWOT method. The results of this research show that an effective marketing strategy used to increase patient satisfaction is at quadrant 1 point, namely supporting aggressive strategies (SO/Strengths and Opportunities) by implementing several strategies, namely (1) By utilizing a strategic location, the clinic can take advantage of various opportunities such as develop services or programs, namely laboratories, midwifery, inpatient services, etc. and carry out promotions via internet media, distribute brochures and put up banners, (2) With strengths such as ambulance facilities, various kinds of patent medicines, home services care/home visits, long-distance consultations provide opportunities to increase patient satisfaction and also increase patient confidence in seeking treatment at the Voluntary Healthy Clinic.